Factors Influencing Unemployment in Indonesia - Fatkhu Rokhim (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study aims to analyze the factors that influence unemployment in Indonesia. This study uses secondary data obtained from the Central Statistics Agency (BPS) and the Investment and Coordinating Board (BKPM). The data used is panel data from time series data for 2015 – 2021 and cross sections covering 34 provinces in Indonesia. The results of the descriptive analysis show that the male unemployment rate tends to be higher each year than that of the female. In addition, the unemployment rate in urban areas tends to be almost two times higher than the unemployment rate in rural areas. The results of the panel data regression analysis show that the variables of economic growth, inflation, wage rates, and the dummy economic crisis during the Covid-19 pandemic have a significant effect on unemployment in Indonesia.